Insect Gut Regeneration. - Zhang, P.; Edgar, B.A. (Cold Spring Harbor perspectives in biology, 2022)
In adult insects, as in vertebrates, the gut epithelium is a highly regenerative tissue that can renew itself rapidly in response to changing inputs from nutrition, the gut microbiota, ingested toxins, and signals from other organs. Because of its cellular and genetic similarities to the mammalian intestine, and its relevance as a target for the control of insect pests and disease vectors, many researchers have used insect intestines to address fundamental questions about stem cell functions during tissue maintenance and regeneration. In Drosophila, where most of the experimental work has been performed, not only are intestinal cell types and behaviors well characterized, but numerous cell signaling interactions have been detailed that mediate gut epithelial regeneration. A prevailing model for regenerative responses in the insect gut invokes stress sensing by damaged enterocytes (ECs) as a principal source for signaling that activates the division of intestinal stem cells (ISCs) and the growth and differentiation of their progeny. However, extant data also reveal alternative mechanisms for regeneration that involve ISC-intrinsic functions, active culling of healthy epithelial cells, enhanced EC growth, and even cytoplasmic shedding by infected ECs. This article reviews current knowledge of the molecular mechanisms involved in gut regeneration in several insect models (Drosophila and Aedes of the order Diptera, and several Lepidoptera).